Pemanfaatan Media Sosial Sebagai Sarana Promosi Makanan Ringan Kripik Singkong di Kabupaten Sampang - Fedianty Augustinah; Widayati Widayati (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2019)
Sampang Regency is one of the districts located on Madura Island, originating from the abundance of cassava plants planted by the community in the area so that many residents process cassava plants into suitable processed materials to be sold as typical or superior food for the community as well as suitable as or typical food from Sampang Regency. The problem is how the use of social media as a means of promoting cassava chips in Sampang Regency can increase sales. The output target to be achieved in this study is publishing in ISSN STIA LAN Bandung Journal. This research is a type of quantitative research, viewed from the level of explanation. This research is an associative study with a form of causal relationship. To answer all research objectives, the analysis is used with a Simple Linear Regression Analysis Model and to test the significance used t test. Research data analysis techniques using simple regression. Suggestions for related offices to assist in the development of the tette chips business in Sampang Regency in optimizing social media for online businesses require training related to marketing and communication marketing through social media.